The Review of Physical Condition Components with Kansetsu Geri Abilities in Karateka - Hudain, Muh Adnan; Sudirman, Sudirman; Sahabuddin, Sahabuddin (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This research is descriptive research that aims to determine the relationship between the results of the analysis of leg explosive power, dynamic balance, and leg split flexibility to the ability of kansetsu Geri against karateka gojukai. The population of this study was Gojukai Soppeng karate athletes with a sample of 30 karatekas. The research variables consist of independent variables, namely leg explosive power, dynamic balance, and leg split flexibility. While the dependent variable is the ability of kansetsu geri against the Gojukai karateka. Based on the results of data analysis, it can be concluded that: (1) There is a relationship between the components of physical condition in terms of the explosive power of the legs with the ability of kansetsu Geri in karateka, with a value of 30.3%. (2) There is a relationship between the physical condition component in terms of dynamic balance and the ability of kansetsu geri in karateka, with a value of 26%. (3) There is a relationship between the physical condition component in terms of leg split flexibility and kansetsu Geri's ability in karateka, with a value of 31.5%. And (4) There is a relationship between the components of physical condition in terms of leg explosive power, dynamic balance and leg split flexibility with the ability of kansetsu Geri in karateka, with a value of 51.9%.